ANALYSIS OF THE LAVENDER MARRIAGE PHENOMENON AND ITS CHALLENGES TO FAMILY LAW IN INDONESIA - Dewi, Tika; Hafifah, Mutia; Marpaung, Watni; Firnanda, Wahyuni; Anastasya, Windy (International Journal of Cultural and Social Science, 2025)
The phenomenon of lavender marriage—a marriage between heterosexual and homosexual individuals based on social or cultural motives to maintain the image or fulfill family expectations—is a real challenge in family law practice in Indonesia. This study aims to analyze the forms, motivations, and legal, social, and psychological implications of this practice. Using a qualitative approach with normative-sociological methods, data were obtained through interviews and literature studies which were then analyzed thematically. The findings show that although lavender marriage is administratively valid, this practice is contrary to the maqashid of marriage according to Islamic law and Law Number 1 of 1974, because it ignores the principles of honesty, the goal of building a family, and protection of partners and children. This study emphasizes the importance of a more adaptive regulatory response and social education to prevent the misuse of the institution of marriage as a tool for identity camouflage. This research contributes to the development of family law policies that are more responsive to contemporary social dynamics.